Efektivitas Pelaksanaan Pembebasan Administratif Bea Balik Nama Kendaraan Bermotor Penyerahan II Dalam Meningkatkan Penerimaan Pajak Daerah Tahun 2018-2020(Studi Pada Pusat Pengelolaan Pendapatan Daerah Wilayah Kota Bekasi) - Jeksi Mukri Artati; Mainita Hidayati (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aims to determine the effectiveness of the implementation of the administrative fee exemption for motor vehicle transfer II in 2018-2020 at the Regional Revenue Management Center (P3DW) of Bekasi City. In this study, the author uses Duncan's theory of effectiveness measurement which includes achievement, goals, integration, and adaptation. The approach used in this study is a qualitative approach with a descriptive method. Data was collected through observation, documentation, and interviews. The results of this study indicate that the implementation of the Administrative Fee Exemption for Motor Vehicle Transfer II (BBN-KB II) in Bekasi City has been effective. This is evidenced by the ability of Bekasi City’s P3DW in realizing tax revenues so that it exceeds the expected target. However, in its implementation, the campaign carried out by P3DW is still lacking because there are still some taxpayers in Bekasi City who are not aware of the program. The obstacles encountered are the financial problems of the taxpayers of motor vehicle transfer II, the lack of campaign and education to taxpayers, the incompleteness of the taxpayer's document requirements because their Motor Vehicle Ownership Book is still with the leasing company.